Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan Pada Pt. Indofood Sukses Makmur Tbk Tahun 2020-2022 - Ekha Ekha; Sabirin Sabirin; Khairina Khairina (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to find out how the company's financial performance at PT. Indofood Sukses Makmur Tbk in terms of liquidity ratios, solvency ratios, profitability ratios and activity ratios. The type of research used in this research is quantitative research with a descriptive approach. The data processed is the financial report of PT. Indofood Sukses Makmur 2020-2022. The analysis technique used is quantitative analysis, which uses a data analysis process in the form of numbers as a tool for analyzing and conducting studies. Then time series analysis is carried out, namely by comparing financial ratio analysis from one period to another, where the ratios used are financial ratio analysis consisting of liquidity ratios, solvency ratios, profitability ratios and activity ratios. from the current ratio and quick ratio, observations are in good condition, from the solvency ratio it is seen that the company is in a healthy condition, and from the profitability ratio it is seen from the net profit margin ratio, return on assets ratio, the company is in good condition and is healthy in gaining profits. And from the activity ratio, seen from the activity turnover ratio and fixed activity turnover ratio, the company is in good condition because the percentage in this ratio increases every year.